Analisa Kedudukan Pemberian Kesaksian Palsu Terhadap Proses Ilmu Forensik dan Tinjauannya Menurut Hukum Islam - Alya Nabila; Ferryal Basbeth; Firman Arifandi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Forensics means taking something to court. This term is commonly used in medicine. Is a scientific process (based on knowledge) in the analysis, collection and presentation of various evidence in the process related to litigation and collection, physical evidence found at the TKP (Case Incident) and then presented in court. False testimony is a statement given by a witness under oath where the contents of the statement contain a meaning that is not in accordance with the truth, in other words, the statement is a lie or fake. Statements whose content is false do not have to be entirely false, but only partially false. Giving false statements is a crime regulated in the provisions of Article 242 of the KUHP concerning perjury and false statements. The purpose of this research is to identify and analyze the position of false testimony in the process of forensic science. In Islam, giving false testimony enters into the sin of associating partners with Allah SWT because of the great harm it causes to society. This study uses a normative juridical method. The search used in this study was Google Scholar, the search application Publish or Perish, and Neliti. From the search results, 995 appropriate journals were obtained and 50 journals were reviewed. This research found that in order to provide a testimony, the witness must provide testimony under oath in accordance with the religion he adheres to, but if the witness continues to give false testimony in court, he is tantamount to breaking his oath and receiving punishment according to Article 242 of the KUHP. Witnesses who give oaths or false statements may have allegations of obstructing the trial process, so this is part of obstruction of justice or an attempt to obstruct the trial and deliberately giving false statements is strictly regulated in Article 242 of the Criminal Code (KUHP)